Exploring the Role of Social Comparison: Unraveling the Influence of Malicious Envy and Materialism on Impulse Buying, with Promotional Campaigns as a Moderator (Journal of Asian Development Studies, 2024)
This paper empirically tests the association between social comparison, malicious envy, and materialism in impulse buying, with promotional campaigns as a moderator. The sample was drawn from retail customers who frequently buy shoes and clothing. The sample size was 302, using a convenience sampling technique, and the data was collected through a survey questionnaire containing 28 items, with responses ranging from strongly agree to strongly disagree. SEM-PLS 4.0 was used for data analysis and to determine the construct reliability and validity. After examination, it was established that social comparison is positively linked to materialism, malicious envy, and impulse buying. Promotional campaigns moderate the relationship between social comparison and impulse buying. However, neither materialism nor malicious envy impact impulse buying, nor do these two mediate the link between social comparison and impulse buying. The study is unique as it has utilized promotional campaigns as moderators, which has never been studied in this context. Also, the findings are valuable for both marketers and consumers to better predict and manage consumption behavior.